A Cross Sectional Study to Assess Peak Expiratory Flow Rate in Healthy School Children for Establishment of Normative Data - Sharma, Rajeev; Kaur, Avneet; Gupta, Manish; Kaur, Amarpreet; Arora, Hobinder; Singh, Sukhpal (Journal of Nepal Paediatric Society, 2020)
Introduction: Peak Expiratory Flow Rate (PEFR) can be measured by cheap and portable instrument, peak flowmeter which is useful in detecting early asthmatic changes and monitoring the treatment response. Methods: This study was conducted on 1000 normal healthy children of nine to 14 years of age of either sex from various schools of Faridkot district in South West Punjab, India. Anthropometry was done and PEFR was measured using Mini Bell Peak Flow Meter. Linear regression analysis was done and normograms were constructed. Results: Linear regression equations were derived for PEFR with height, weight, BSA and BMI in boys and girls. The most significant correlation was seen with height (r = 0.527 in boys, r = 0.410 in girls) followed by body surface area (r = 0.506 in boys, r = 0.296 in girls). Body mass index had negative correlation (r = -0.200) with PEFR in girls. Nomograms were constructed on basis of linear regression equations of PEFR with height (-46.67 + 2.02 x height for boys, -12.64 + 1.50 x height for girls) and BSA (82.02 + 137.2 x BSA for boys, 96.61 + 88.11 x BSA for girls) Conclusion: There is need for nomogram for each region so that personal value of PEFR can be compared to normal reference population and also with predicted value from regression equation as PEFR varies from region to region. The nomograms and regression equations derived from this study can be useful for predicting normal values of PEFR of children of South West Punjab.